Pengaruh Pengasapan (Thermal Fogging) Insektisida Piretroid (Malation 95%) Terhadap Nyamuk Aedes aegypti dan Culex quinquefasciatus di Pemukiman - Hasan Boesri; Damar Tri Boewono (Loka Litbang Kesehatan Pangandaran, 2009)
Abstracts. The evaluation of piretroid insecticide (active ingredient Malation 95%) was conductedin Sub district Tengarang, Semarang Segency, Central Java Province. The insecticidewas applied using thermal fogging method for dosages of 125, 250, 375, 500 and 625ml/ha (diluted in diesel to 10 litters).The evaluation of the efficacy was conducted against two mosquito species, Aedes aegypti(the main dengue haemorrhagic fever) and Culex quinquefasciatus (the urban lymphatic filariasisvector).Result of the evaluation was revealed that dosages of 500 and 625 ml/ha were effectiveagainst both tested mosquito species indoor and outdoor